2006
DOI: 10.1111/j.1420-9101.2006.01087.x
|View full text |Cite
|
Sign up to set email alerts
|

Rampant host switching and multiple female body colour transitions in Philotrypesis (Hymenoptera: Chalcidoidea: Agaonidae)

Abstract: Figs (Ficus, Moraceae) and their associated fig waSPS (Hymenoptera, Chalcidoidea and Agaonidae) have attracted much attention and have been used as a model system for many studies. Fig waSPS belonging to the genus Philotrypesis are very common in most figs but their taxonomy, ecology and biology are currently poorly explored. A previous study on African Philotrypesis showed that their host association is phylogenetically conserved at subsection level. We reconstructed a molecular phylogeny with extended sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…Regarding mean parasitism rates, about 20% of S. nonagrioides larvae were successfully parasitized by C. typhae . The same mean value or range of parasitism rates were observed in stem borers parasitized by C. sesamiae , and by C. flavipes , in maize and sorghum in Kenya (Mailafiya et al 2010), and by C. chilonis in rice in China (Lou et al 2014), but lower values were also observed (Jiang et al 2006). This mean value is much lower than that observed in laboratory conditions.…”
Section: Discussionsupporting
confidence: 58%
“…Regarding mean parasitism rates, about 20% of S. nonagrioides larvae were successfully parasitized by C. typhae . The same mean value or range of parasitism rates were observed in stem borers parasitized by C. sesamiae , and by C. flavipes , in maize and sorghum in Kenya (Mailafiya et al 2010), and by C. chilonis in rice in China (Lou et al 2014), but lower values were also observed (Jiang et al 2006). This mean value is much lower than that observed in laboratory conditions.…”
Section: Discussionsupporting
confidence: 58%
“…This pattern indicated that the mitochondrial genomes of Philotrypesis either evolved rapidly or that the species diverged long ago. The former explanation seemed more likely because: 1) some of the genes were similar or even identical between the two species; 2) previous phylogenetic results based on the combination of mitochondrial ( cob ) and nuclear ( ITS2 ) markers indicated that the two species may be sister taxa [23]; 3) morphological comparisons show that the two species were similar (Figure S2). …”
Section: Resultsmentioning
confidence: 99%
“…Several studies have compared the phylogenies of regional NPFW radiations with phylogenies of their Ficus or insect hosts (Machado et al , 1996; Lopez‐Vaamonde et al , 2001; Weiblen & Bush, 2002; Jackson, 2004; Jousselin et al , 2004; Jiang et al , 2006; Jousselin et al , 2006; Marussich & Machado, 2007; Jousselin et al , 2008; Silvieus et al , 2008). Most of these involve wasps from one or two fig sections, but one study of Asian Philotrypesis wasps, most of which are parasitoids/inquilines of pollinators, found little correspondence between Philotrypesis phylogeny and Ficus sections and the authors argue that ‘rampant host shifting’ has occurred (Jiang et al , 2006). Further studies of both parasitoid and galler taxa across fig sections are needed to test if, for example, host switching is more common for parasitoids than gallers.…”
Section: Cospeciation Of Npfw and Hostsmentioning
confidence: 99%